Combating COVID-19: MVA Vector Vaccines Applied to the Respiratory Tract as Promising Approach Toward Protective Immunity in the Lung - Förster, Reinhold; Fleige, Henrike; Sutter, Gerd (Frontiers in Immunology, 2020)
The lung is the vital target organ of coronavirus disease 2019 (COVID-19) caused by infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). In the majority of patients the most active virus replication seems to be found in the upper respiratory tract, severe cases however suffer from SARS-like disease associated with virus replication in lung tissues. Due to the current lack of suitable anti-viral drugs the induction of protective immunity such as neutralizing antibodies in the lung is the key aim of the only alternative approach – the development and application of SARS-CoV-2 vaccines. However past experience from experimental animals, livestock and humans showed that induction of immunity in the lung is limited following application of vaccines at peripheral sides such as skin or muscles. Based on several reflections we therefore propose here to consider the application of a modified vaccinia Ankara (MVA)-based vaccine to mucosal surfaces of the respiratory tract as a favourable approach to combat COVID-19.